MORPHOLOGICAL FEATURES OF THE STROMAL COMPONENT OF THE LIVER IN EXPERIMENTAL SUPPLEMENT OF RATIONS WITH FOOD ADDITIVES - Mustafina, Н.M.; Starchenko, I.I.; Koka, V.М.; Fylenko, B.М.; Roiko, N.V.; Cherniak, V.V.; Prylutskyi, O.K. (World of Medicine and Biology, 2022)
The purpose of this study was to study in an experiment the morphological features of the structural organization of the periportal connective tissue of the liver of white rats after the introduction into the diet of a complex of food additives (sodium glutamate, sodium nitrite, Ponceau 4R) for 8 weeks. The study was performed on 30 outbred white rats of both sexes, weighing 204±0.67 g. The experimental animals were additionally fed a combination of food additives – monosodium glutamate, Ponceau R-4, sodium nitrate for 1 and 8 weeks. The study of the stromal component of the liver was carried out on traditional histological preparations. To differentiate immunocompetent cells of connective tissue structures, immunohistochemical reactions with antibodies to CD68 and CD3 were performed. It was established that the addition of a complex of food additives (sodium glutamate, sodium nitrite, ponzo 4R) to the standard diet of laboratory animals for 8 weeks leads to excessive development of connective tissue in the liver and changes in the relative number of CD3+ and CD68+ cellular elements.
Keywords: liver; connective tissue; stroma; food additives; monosodium glutamate; Ponceau R-4; sodium nitrate